KNOWLEDGE, ATTITUDE AND PRACTICE ABOUT SKIN CANCER AND ITS PREVENTION AMONG IIUM KUANTAN UNDERGRADUATE STUDENTS - BINTI SAZALI, NUR ANIS AMIRA; BINTI MOHAMMAD, MARDHIAH (International Journal of Allied Health Sciences, 2023)
Introduction: The worldwide incidence of skin cancer has been rising for the past decades that at least two million of non-melanomas and 100,000 of melanomas occur every year. In Malaysia, there are 212 deaths related to skin cancer that were reported in 2018. Skin cancer is mainly caused by the exposure to ultraviolet light that most undergraduate students in IIUM Kuantan are exposed to as they commute to teaching and learning venue. The Malaysian Meteorological Department reported that the east coast region receives 50% sunny weather yearly as compared to other parts of Malaysia. Hence, the main objective of this research was to assess the level of knowledge, attitude and practice about skin cancer and its prevention among IIUM Kuantan undergraduate students. Methods: A cross-sectional study using convenience sampling method was conducted to collect data from 129 respondents. The questionnaire was adapted and modified before being distributed through Google form to the participants. Results: Overall, the level of knowledge, attitude and practice about skin cancer and its prevention among IIUM Kuantan undergraduate students was moderate. Mann-Whitney test and Kruskal-Wallis test performed revealed a significant association of level of knowledge between gender (p = 0.020) and exposure to direct sunlight (p = 0.050). Similarly, a significant association was observed in attitude as well as practice of skin cancer prevention between gender (p<0.001). Spearman correlation showed a positive correlation between knowledge and attitude and attitude and practice about skin cancer and its prevention. Conclusion: IIUM Kuantan undergraduate students have a moderate level for knowledge, attitude and practice about skin cancer and its prevention. There was an association of level of knowledge with gender and exposure to direct sunlight. However, only gender associate with the level of attitude and practice. This study found a positive correlation between knowledge and attitude and attitude and practice. This research is expected to provide more insight into overall awareness regarding skin cancer among the IIUM Kuantan undergraduate students which might serve as a benchmark for more related research in the future.